2011
DOI: 10.1007/s11368-011-0409-5
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and glufosinate-based herbicides: fate in soil, transfer to, and effects on land snails

Abstract: International audiencePurpose The aim of this work was to assess the transfer and effects of two widely used herbicides on the land snail Helix aspersa during long-term exposure under laboratory conditions. Materials and methods Newly hatched snails were exposed for 168 days to soil and/or food contaminated with a formulation of glyphosate (Bypass®) or glufosinate (Basta®) at the recommended field doses and also at 10-fold this dose. Results and discussion Herbicide degradation patterns showed that snails we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…It has been suggested that the same function POEA provides, by enhancing glyphosate transport into plant cells, also facilitates increased permeability in animal cells (Hedberg and Wallin, 2010). The potential for bioaccumulation of glyphosate has also been observed in terrestrial snails (Helix aspersa) fed a diet contaminated with glyphosate (Druart et al, 2011), water hyacinth (Eichhornia crassipes) exposed to pure glyphosate, and also in tissue of carp (Cyprinus carpio) and tilapia (Oreochromis mossambicus) that were exposed to environmentally relevant concentrations (Wang et al, 1994). Taken together, these results support the possibility of food chain contamination.…”
Section: Exposure To Glyphosate and Metabolites In Aquatic Environmentmentioning
confidence: 99%
“…It has been suggested that the same function POEA provides, by enhancing glyphosate transport into plant cells, also facilitates increased permeability in animal cells (Hedberg and Wallin, 2010). The potential for bioaccumulation of glyphosate has also been observed in terrestrial snails (Helix aspersa) fed a diet contaminated with glyphosate (Druart et al, 2011), water hyacinth (Eichhornia crassipes) exposed to pure glyphosate, and also in tissue of carp (Cyprinus carpio) and tilapia (Oreochromis mossambicus) that were exposed to environmentally relevant concentrations (Wang et al, 1994). Taken together, these results support the possibility of food chain contamination.…”
Section: Exposure To Glyphosate and Metabolites In Aquatic Environmentmentioning
confidence: 99%
“…The discovery of glyphosate in the body of the land snail Cornu aspersum (O.F. Müller) by Druart et al 11. suggested the ability of this herbicide to enter the food chain.…”
mentioning
confidence: 99%
“…Glyphosate is traditionally considered to be a chemical with relatively low ecological and toxicological side effects in terrestrial ecosystems 4 6 10 because the active ingredient inactivates rapidly when it reaches the soil surface 4 9 11 , but in aquatic environments it is known to be highly toxic 12 and recently it became suspected to be carcinogenic to humans 13 . Commercial products containing glyphosate seem to be more toxic than the active ingredient alone, possibly due to the surfactants used in the commercial solutions 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Used within recommended rates, glyphosate has little or no effects on non-target organisms (Franz et al, 1997). However, excessive use of glyphosate is reported to have adverse effects on metabolic functions of both unicellular organisms (Austin et al, 1991;Zobiole et al, 2011;Shehata et al, 2013;Newman et al, 2016) and wide range of multicellular organisms such as algae (Oliveira et al, 2016), earthworms (Santadino et al, 2014), arthropods (Pérez et al, 2011), honey bees (Balbuena et al, 2015), snails (Druart et al, 2011), fish (Hued et al, 2012), frogs (Pérez -Iglesias et al, 2016, Mann andBidwell, 1999), lizards (Schaumburg et al, 2016), birds (Oliveira et al, 2007), swine (Lee et al, 2009) and humans (Samsel and Seneff, 2013).…”
Section: Introductionmentioning
confidence: 99%